GRAFTS COMPARISON BETWEEN QUADRICEPS TENDON AUTOGRAFT VS. ALLOGRAFT FOR ANTERIOR CRUCIATE LIGAMENT REVISIOON RECONSTRUCTION: A LITERATURE REVIEW - Halim Hasibuan, Ariq Muflih; Yudhadibrata, Permana (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Anterior cruciate ligament (ACL) reconstruction is one of the most common orthopaedic surgeries performed on active people in the world. One of the most important surgical decisions is graft type for use in the reconstruction. Recently, the quadriceps tendon has gained popularity for use as a graft source for ACL reconstruction. The graft choice is broadly between an autograft or allograft. This review aims to understand the current concepts in graft comparison between quadriceps tendon autograft vs. allograft for anterior cruciate ligament revision reconstruction.Methods: This literature review study was reported following the preferred reporting items for systematic reviews and adhered to a structured review protocol. The author searched the PubMed, ScienceDirect, and British Medical Journal databases. The authors comparing selected publications reporting patient outcomes with all types of reviews or descriptions of ACL revision reconstruction and its graft being used or other related subjects. Published in English is included. The author then formulates a synthesis to support the previously determined research objectives.Results: ACL reconstruction with partial thickness soft tissue quadriceps tendon graft is a reliable option. Where there are differences in the failure rates of ACL reconstructions between allografts and autografts, these can mostly be explained by irradiated grafts. Giving sufficient radiation to achieve sterility will likely weaken grafts and make them more likely to fail; therefore, irradiating grafts is not recommended. The evidence shows no significant differences in clinical effectiveness between autografts and non-irradiated allografts. Failure rates with both grafts are now low.Discussion: The primary goals of rehabilitation after ACL reconstruction do not vary considerably based on graft type and emphasize: (1) restoration of the full range of motion, (2) normalization of quadriceps strength, (3) improvement of overall lower extremity muscle strength, and (4) re-training of movement patterns to return to pre-injury sports participation while decreasing injury risk. Achieving full motion and quadriceps strength contributes to a rapid return to normal weight bearing, gait, and activities of daily living. In the setting of revision ACL reconstruction, there are various considerations regarding graft choice due to tunnel size or position, previous usage of other grafts, and reconstructions in the other leg, which may mean that allografts would be preferred to autografts. The other population not covered sufficiently in the literature is the elite sprinting athlete, where autograft choices may be influenced by the effect of graft harvesting on their sport. However, in most cases, allograft ACL reconstruction with non-irradiated grafts is as safe but more expensive than autograft ACL reconstruction, which is preferred as it is more cost-effective.Conclusion: There is little difference in the results of ACL reconstruction with autografts or non-irradiated allografts, with any advantage being with autografts. The cost is higher with allografts. So if autografts are available, allografts are not cost-effective.